Evaluation of hepatic functional reserve of hepatocellular carcinoma (≤ 5 cm) by liver shear wave velocity combined with multiple parameters - Yang, Long; Zhu, Haohui; Zhang, Xijun; Fu, Xiaobing; Zhao, Xiaojuan; Wang, Xiaojing; Ren, Xiaozhuan; Yu, Haibo; Yuan, Jianjun (Frontiers in Oncology, 2024)
Background: Normal hepatic functional reserve is the key to avoid liver failure after liver surgery. This study was to investigate the assessment of hepatic functional reserve using liver shear wave velocity (LSWV) combined with biochemical indicators, tumor volume, and portal vein diameter.In this single-center prospective study, a total of 123 patients with hepatocellular carcinoma (HCC) were divided into test group (n=92) and validation group (n=31). All patients were Child-Pugh grade A. The indocyanine green retention rate at 15 min (ICG-R15), liver shear wave velocity (LSWV), portal vein diameter (Dpv), alanine aminotransferase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), γ-glutamyl transpeptidase (γ-GGT), albumin (ALB) and prothrombin time (PT) and also liver tumor volume (maximum diameter ≤5 cm) were measured. In test group, multiple parameters were used to evaluate hepatic functional reserve, and the multiparametric model was established. The receiver operating characteristic (ROC) curve analysis was conducted to assess the diagnostic performance of the multiparametric model. In validation group, the predictive effectiveness of multiparametric model was analyzed by consistency test.Results: It was revealed that LSWV, ALB, and PT were statistically significant in evaluation of the hepatic functional reserve (P<0.05). The multiparametric model was formulated as follows: Y= -18.954+9.726*LSWV-0.397*ALB+2.063*PT. The value of area under the curve (AUC) for the multiparametric model was 0.913 (95% confidence interval (CI): 0.835-0.962, P < 0.01), with the cut-off value of 16.656(sensitivity, 0.763; specificity, 0.926).The Kappa value of consistency test was 0.655(P<0.01).Conclusions: LSWV combined with ALB and PT exhibited a high predictive effectiveness for the assessment of hepatic functional reserve, assisting clinical diagnosis and management of liver diseases.